Cough-Associated Headache in Patients with Chiari I Malformation: CSF Flow Analysis by Means of Cine Phase-Contrast MR Imaging - Bhadelia, R.A.; Frederick, E.; Patz, S.; Dubey, P.; Erbay, S.H.; Do-Dai, D.; Heilman, C. (American Journal of Neuroradiology, 2011)
SUMMARY: The purpose of this study was to analyze the CSF flow in patients with Chiari I to determine differences between patients with and without CAH. Thirty patients with Chiari I malformation underwent cine-PC CSF flow imaging in the sagittal plane. CSF flow pulsations were analyzed by placing regions of interest in the anterior cervical subarachnoid space. Maximum CSF systolic (craniocaudal) and diastolic (caudocranial) velocities as well as the durations of CSF systole and diastole (measured in fractions of the cardiac cycle) were determined. In the region of interest just below the foramen magnum, patients with CAH had a significantly shorter CSF systole and longer diastole (P = .02). A CSF diastolic length of ≥0.75 of the cardiac cycle was 67% sensitive and 86% specific for CAH. Our results indicate that Cine-PC imaging can show differences in CSF flow patterns in patients with Chiari I with and without CAH. CAHcough-associated headacheCine-PCcine phase-contrastCSF diastoleduration of CSF diastolic flow (fraction of the cardiac cycle)CSF systoleduration of CSF systolic flow (fraction of the cardiac cycle)MSVmaximum systolic velocity (millimeters/second)MDVmaximum diastolic velocity (millimeters/second)